Mechanisms controlling Th17 cytokine expression and host defense - McAleer, Jeremy P. (Society for Leukocyte Biology, 2011)
Th17 cells contribute to mucosal immunity by stimulating epithelial cells to induce antimicrobial peptides, granulopoiesis, neutrophil recruitment, and tissue repair. Recent studies have identified important roles for commensal microbiota and Ahr ligands in stabilizing Th17 gene expression in vivo, linking environmental cues to CD4 T cell polarization. Epigenetic changes that occur during the transition from naïve to effector Th17 cells increase the accessibility of il17a, il17f, and il22 loci to transcription factors. In addition, Th17 cells maintain the potential for expressing T-bet, Foxp3, or GATA-binding protein-3, explaining their plastic nature under various cytokine microenvironments. Although CD4 T cells are major sources of IL-17 and IL-22, innate cell populations, including γδ T cells, NK cells, and lymphoid tissue-inducer cells, are early sources of these cytokines during IL-23-driven responses. Epithelial cells and fibroblasts are important cellular targets for IL-17 in vivo; however, recent data suggest that macrophages and B cells are also stimulated directly by IL-17. Thus, Th17 cells interact with multiple populations to facilitate protection against intracellular and extracellular pathogens.